The Standard of Proof in Lithuanian Civil Proceedings - Bartkus, Jurgis (Teisė, 2026)
The aim of this article is to review the standard of proof applied in Lithuanian civil proceedings. The article analyses the concept, function, and types of the standard of proof. An analysis of statutory law, court practice, and legal scholarship reveals that the Lithuanian civil procedure has long lacked a uniformly applied standard of proof. The article demonstrates that the 2024 decision of the Supreme Court of Lithuania significantly influenced the application of a uniform standard of proof, leading courts to apply the reasonable belief standard more frequently thereafter.
Keywords: standard of proof; civil procedure; evidence; cognitive bias